Basal Synaptic Transmission and Long-Term Plasticity at CA3-CA1 Synapses Are Unaffected in Young Adult PINK1-Deficient Rats - Memon, Adeel A.; Bagley, Micah E.; Creed, Rose B.; Amara, Amy W.; Goldberg, Matthew S.; McMahon, Lori L. (Frontiers in Neuroscience, 2021)
Loss of function mutations in PARK6, the gene that encodes the protein PTEN-induced kinase 1 (PINK1), cause autosomal recessive familial Parkinson’s disease. While PD is clinically diagnosed by its motor symptoms, recent studies point to the impact of non-motor symptoms, including cognitive dysfunction in the early pre-motor stages of the disease1,2. As the hippocampus is a key structure for learning and memory, this study aimed to determine whether synaptic transmission is affected at CA3-CA1 excitatory synapses in PINK1 knockout rats at an age when we recently reported a gain of function at excitatory synapses onto spiny projection neurons in the dorsal striatum3 and when motor symptoms are beginning to appear4. Using extracellular dendritic field excitatory postsynaptic potential recordings at CA3-CA1 synapses in dorsal hippocampus from 4 to 5-months-old PINK1 KO rats and wild-type littermate controls, we observed no detectable differences in the strength of basal synaptic transmission, paired-pulse facilitation, or long-term potentiation. Our results suggest that loss of PINK1 protein does not cause a general dysfunction of excitatory transmission throughout the brain at this young adult age when excitatory transmission is abnormal in the striatum.